Durability of natural fiber-reinforced composites of ethylene-propylene copolymer under accelerated weathering and composting conditions - Kumar, A. P.; Depan, Dilip; Singh, R. P. (Journal of Thermoplastic Composite Materials, 2005)
Three types of composites are prepared by the melt mixing of ethylene-propylene copolymer (EPC) with (i) 3 % NaOH-treated jute fiber, (ii) 17.5 % NaOH-treated jute fiber, and (iii) commercial microcrystal line cellulose powder using maleated EPC as compatibilizer. The composites obtained are characterized by FTIR and microscopic measurements. Their mechanical properties are measured using a UTM (Instron model 4204). The durability of the composites is evaluated in an irradiation chamber with UV radiation of wavelength lambda >= 290 mn and composting conditions at different time intervals. The composites made from microcrystalline cellulose show superior mechanical properties, biodisintegrability, as well as photoresistance whereas the specimen containing 3% NaOH-treated fiber exhibited the lowest photoresistance. Increasing the quantity of maleated EP (MEP) in the composition decreases photostability. Neat EPC has been found to be highly stable than all the composites with increasing UV irradiation. It has been found that the composites are less durable under both abiotic and biotic conditions in comparison to the neat polymer.
Keywords: compatibilization; composites; jute fiber; mechanical properties; Microcrystalline cellulose; photodegradation and composting

Recent advances in biodegradable nanocomposites - Pandey, J. K.; Kumar, A. P.; Misra, M.; Mohanty, A. K.; Drzal, L. T.; Singh, R. P. (Journal of Nanoscience and Nanotechnology, 2005)
There is growing interest in developing bio-based products and innovative process technologies that can reduce the dependence on fossil fuel and move to a sustainable materials basis. Biodegradable bio-based nanocomposites are the next generation of materials for the future. Renewable resource-based biodegradable polymers including cellulosic plastic (plastic made from wood), corn-derived plastics, and polyhydroxyalkanoates (plastics made from bacterial sources) are some of the potential biopolymers which, in combination with nanoclay reinforcement, can produce nanocomposites for a variety of applications. Nanocomposites of this category are expected to possess improved strength and stiffness with little sacrifice of toughness, reduced gas/water vapor permeability, a lower coefficient of thermal expansion, and an increased heat deflection temperature, opening an opportunity for the use of new, high performance, lightweight green nanocomposite materials to replace conventional petroleum-based composites. The present review addresses this green material, including its technical difficulties and their solutions.
Keywords: cellulose; layered silicates and properties; Nanocomposite; poly(caprolactone)s; poly(hydroxy alkanoate)s; polyiactic acid; Starch

Synthesis, characterization, and performance evaluation of novel stabilized TDI-based polyurethane coatings under accelerated weathering - Kumar, A. P.; Reddy, K. R.; Rana, S.; Lonkar, Sunil P.; Raut, K. G.; Singh, R. P. (Journal of Vinyl & Additive Technology, 2005)
Some toluene dilsocyanate (TDI)-based polyurethane resins (PURs) for coating applications were synthesized with castor oil and their performance was estimated under accelerated UV weathering with and without a novel UV absorber. Changes in physical properties, chemical structure, and color of the samples were monitored by mechanical property testing, FTIR spectroscopy, and colorimetry, respectively. A stable polyurethane coating was achieved at 0.5% concentration of additive in the host matrix. Mechanical properties were also retained as in the pristine PUR after mixing. Commercial Tinuvin P and benzotriazole-based novel UV absorbers were found to improve the photoresistance of the PUR coating, and the highest efficiency of the novel UV absorber against weathering was estimated at 0.5 wt% concentration.(c) 2005 Society of Plastics Engineers.

Biodegradation of gamma-sterilised biomedical polyolefins under composting and fungal culture environments - Alariqi, Sameh A. S.; Kumar, A. P.; Rao, B. S. M.; Singh, R. P. (Polymer Degradation and Stability, 2006)
Polyolefin-based commodities are widely used as biomedical devices and food packaging after gamma-sterilisation. The aim of the present work was to study the effect of gamma-sterilisation on the biodegradation of polyolefins. Films of isotactic polypropylene, high-density polyethylene and ethylene-propylene (EP) copolymers were sterilised under gamma-radiation with doses of 10 and 25 kGy. Neat and sterilised samples were incubated in compost and fungal culture environments. The changes in functional groups, surface morphology and chain scission in polymer chains were characterized by FTIR spectroscopy, SEM and viscometric measurements, respectively. A gradual decrease in intrinsic viscosity [eta] and increase in carbonyl and hydroxyl regions in FTIR spectra were found for the gamma-sterilised samples as a function of increasing dose. Polypropylene was found to be more susceptible to both radio-oxidation and biodegradation. It was observed that in case of ethylene-propylene copolymers, extent of gamma-sterilisation and/or biodegradation depends on the composition and distribution of comonomers. Important surface erosion was detected by SEM, for higher sterilisation doses, after composting. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Biodegradation; chain scission; Composting and fungal culture; gamma-sterilisation; Polyolefins